0292 Baseline Pro-Inflammatory Cytokine and Cortisol Levels Differentially Predict Mood Disturbance and Working Memory Deficits Induced by Chronic Sleep Restriction. (27th May 2020) - Jones, C W; Kaizi-Lutu, M; Mange, A; Basner, M; Dinges, D F
Abstract: Introduction: Sleep restriction disturbs mood, impairs neurocognitive performance, and elevates proinflammatory cytokine levels. However, whether basal inflammation influences mood and neurocognitive performance across sleep restriction is unknown. This study examines whether baseline IL-6, cortisol, and TNF-α levels predict the deterioration of mood and working memory performance across sleep restriction. Methods: N=124 healthy participants (52% female; n=64), 22–45 years of age, had valid protein, mood, and working memory data. The study included two baseline nights (8h time in bed [TIB]) followed by five nights of 4h TIB. Venous blood was collected on the second baseline day and IL-6, cortisol, and TNF-α levels were measured via commercially available ELISA assays. The profile of mood states (POMS) and the digit span test (DST) were completed every 2h during wakefulness and daily averages were computed. Mixed-effects multi-level models, adjusted for baseline, evaluated the main effect of IL-6, cortisol, and TNF-α levels on the POMS and DST independently and examined the trajectory of POMS and DST by the interaction of protein levels and day of sleep restriction. Results: At baseline, IL-6, cortisol, and TNF-α levels were not associated with POMS or DST. There was a main effect of IL-6, but not cortisol or TNF-α, levels on mood disturbance (β=3.811; P=0.015); IL-6 levels did not predict the trajectory of mood across sleep restriction (β=0.187; P=0.57). Higher baseline cortisol levels predicted increasing mood disturbance across days (β=-1.329; P<0.0001). Higher baseline TNF-α levels predicted degrading DST performance across days (β=-0.313; P=0.020). Higher IL-6 (β=-0.246; P=0.010) and lower cortisol (β=0.185; P=0.037) levels also predicted degrading DST performance across days. Conclusion: The study findings suggest that basal inflammatory cytokine and cortisol levels are implicated in the individual risk of mood disturbance and working memory deficits resulting from chronic sleep restriction and highlight the need to consider biological processes and phenotypes together. Support: This work was supported by National Institute of Health NIH R01NR004281 and National Space and Biomedical Research Institute NSRBI NCC 5–98.